Информационная технология анализа медиапространства на основе системы NEWSCAPE - Малышко, С.А. (Управляющие системы и машины, 2017)
Описана информационная технология анализа медиапространства на основе системы NEWSCAPE, формализованы основные этапы сравнительного анализа объектов в информационном пространстве; предложены их математически вычисляемые характеристики, положенные в основу многофакторного анализа объектов посредством информационно-аналитической системы. Описано інформаційну технологію аналізу медіапростору на основі системи NEWSCAPE, формалізовано основні етапи порівняльного аналізу об'єктів в інформаційному просторі; запропоновано їх математично обчислювальні характеристики, покладені в основу багатофакторного аналізу об'єктів за участі інформаційно-аналітичної системи. Purpose. The paper describes the main features and the peculiarities of information technology of the media space analysis on the basis of the “NEWSCAPE” system, which form the basis for multifactor analysis of the objects using the information-analytical system. Methods. The basic stages of the information space analysis are: the formation of a subset of the media space for analysis, the extraction of information from a subset, the information specification, the benchmarks calculation, the calculation of the relative indicators, the information evaluation, the information links construction, in-depth analysis of information, assessment and refinement of the information sources variety, analysis of the information space. Results. The main stages of the comparative analysis of objects in the media space are formalized and the mathematically calculated characteristics are presented. These results form the basis for the creation of analytical tools for the NEWSCAPE information and analysis system, and its practical application has confirmed their effectiveness.